Vitamin D supplementation changed relationships, not levels of metabolic-hormonal parameters in autoimmune thyroiditis - Vondra, K; Bílek, R; Matucha, P; Salátová, M; Vosátková, M; Stárka, L; Hampl, R (Physiological research, 2017)
In women with chronic autoimmune thyroiditis and vitamin D deficiency we have found reference levels of relevant metabolic-hormonal parameters except for parathormone and total calcium. Three months supplementation with vitamin D (4300 IU/day, cholekalciferol) did not lead to significant changes of investigated hormonal parameters, while the levels of parathormone and calcium reached normal levels. However, a correlation analysis revealed marked changes in mutual relations. First, an inverse correlation of vitamin D with parathormone, insulin secretion (C peptide, insulin) and its efficiency (HOMA IR) disappeared. Relationships of vitamin D to hepatic insulin resistance (insulin/C peptide), to DHEA (both negative), and to DHEAS/DHEA ratio (positive) were newly found. Second, a positive correlation of CRP with insulin secretion remained, while its relation to insulin efficiency (HOMA IR, insulin/C peptide) was newly observed. Analogical positive correlations appeared also among anti TPO and insulinemia, insulin/C peptide, HOMA IR, and anti Tg to C peptide. A relationship of the CRP with anti TPO became significant (+). Third, out of glucose metabolism parameters only insulin/C peptide and glycemia did not correlate with vitamin D during its deficiency, while after supplementation insulin/C peptide alone correlated positively with both DHEAS and DHEA, and negatively with vitamin D.
Keywords: potravní doplňky; Dietary Supplements; krevní glukóza; Adult; Humans; dospělí; lidé; Blood Glucose; ženské pohlaví; nedostatek vitaminu D; lidé středního věku; autoimunitní tyreoiditida; Female; Thyroiditis, Autoimmune; Vitamin D; vitamin D; Vitamin D Deficiency; Middle Aged